Soil Organic Carbon Storage of Different Soil‐Sized Fractions in Perennial Bioenergy Crops on Marginally Productive Cropland in Southern Canada - Augustine K. Osei; Naresh V. Thevathasan; Maren Oelbermann (GCB Bioenergy)
ABSTRACT Understanding carbon (C) storage in different soil‐sized fractions of perennial bioenergy crops enhances our knowledge of how these crops contribute to long‐term soil organic carbon (SOC) storage, with positive implications for mitigating climate change through C sequestration. However, the extent to which perennial bioenergy crops contribute C in different soil‐sized fractions remains unclear. Hence, this study investigated SOC contents under perennial bioenergy crops of Miscanthus (Miscanthus × giganteus L.), willow (Salix miyabeana L.), switchgrass (Panicum virgatum L.), and a successional site. We also quantified the C contribution of the bioenergy crops to different soil‐sized fractions using the δ13C natural abundance technique. After 12 years of cultivation, SOC contents to 30 cm depth increased by 2.5% and 3.1% in willow and Miscanthus, respectively, but decreased by 3.7% in switchgrass compared to baseline SOC data. SOC stocks ranged from 5686 to 7002 g C m−2 and were higher (p ≤ 0.050) in the successional site compared to switchgrass and willow, but not Miscanthus. Unlike switchgrass and willow, Miscanthus maintained SOC stocks comparable to the successional site even with annual biomass harvest. This implies that the ability of perennial bioenergy crops to influence SOC storage similar to regrowth vegetation on marginally productive cropland depends significantly on the crop species. Additionally, Miscanthus contained higher (p ≤ 0.013) SOC in micro‐sized and silt + clay fractions at 20–30 cm depth compared to the 0–10 and 10–20 cm depths and contributed the most C in all three soil‐sized fractions compared to switchgrass and willow. Our findings suggest that among the three bioenergy crops, Miscanthus has the greatest potential for long‐term C storage and stabilization in deeper soil depths on marginally productive croplands. This holds true even with annual biomass harvesting and the absence of fertilization, making Miscanthus a valuable contributor to climate change mitigation.